Implementation of ETAT (Emergency Triage Assessment And Treatment) in a central hospital in malawi. (4th April 2011) - Robison, J; Ahmed, Z; Durand, C; Nosek, C; Namathanga, A; Milazi, R; Thomas, A; Mwansambo, C; Kazembe, P N; Torrey, S
Abstract : Aims: The Under 5 clinic in this busy central hospital in Malawi is the initial point of care for acutely ill children who require admission; 200–300 children are seen in the clinic each day and up to 45 of these are admitted. Prior to September 2009 there was no formal triage system and patients were rarely stabilised prior to transfer to the wards. In patient mortality were approximately 8%; 59% of those deaths occurred <24 h from admission. Methods: In September 2009 a multidisciplinary team (comprising local healthcare workers and clinicians from the UK and USA) worked to implement the WHOs ETAT (Emergency Triage Assessment and Treatment) system into the Under 5 clinic. They trained local staff in ETAT, implemented an improved system for patient flow, established a emergency room for treatment of critically ill patients and a system of senior support for the clinicians in the Under 5 clinic. Data on admissions and mortality were analysed before and after implementation of ETAT. Results: Admissions remained comparable before and after ETAT (17 452 vs 17 939). Quarterly mortality reduced from 9.3% and 7.9% for the quarters before implementation of ETAT to 8.7% and 7.1% after ETAT. Early mortality (in first 48 h following admission) improved in Q1 of 2009 from 61.8% to 53.9% in Q1 of 2010. This trend continued over 2010 with percentage <48 h mortality in Q2 2010 61.8% compared to 63.4% in 2009 and Q3 2010 53.1% compared to 54.9% in Q3 2009. Conclusions: In a busy central hospital in Malawi with limited resources a collaborative effort to train staff in ETAT and thereby improve the assessment and treatment of critically children in Malawi has been associated with improved patient outcomes particularly in mortality at <48 h. This strategy could be used in similar settings in the developing world to improve acute paediatric care.